The recruit [videorecording (DVD)] - Birnbaum, Roger; Donaldson, Roger; Pacino, Al, 1940-; Farrell, Colin, 1976-; Moynahan, Bridget, 1972- (Touchstone Home Entertainment ; Distributed by Buena Vista Home Entertainment, 2003)
Clayton recently completed his studies at MIT. One evening, Clayton is approached by Walter Burke, a recruiter for the CIA, and believes Clayton is just the sort of man the CIA is looking for. Clayton, who has little interest in an ordinary nine-to-five career and accepts the offer. Clayton has to keep in mind Burke's dictum that "nothing is as it seems," especially when Clayton is given a special assignment -- find the mole within the Agency's training program who is actually feeding information to America's enemies.